Characterization of bacteria coliform in smoked and live Asian Clam (corbicula fluminea) sold in Kota Bharu, Kelantan. - Zalina Che Manan (2014)
Up to date, there is no database information on the characterization of bacteria coliform isolated from smoked and live Asian Clam (Corbicula fluminea) in Malaysia. Thus, this study was carried out to provide information on phenotyphic characteristics, antibiogram and heavy metal resistance pattern, as well as the genotypes of the bacteria coliform. Current database information may useful for future studies in clinical analysis especially in epidemiological study, prophylactic purposes, and public health management plans. Bacteria coliform were isolated from smoked and live Asian Clam using Eosin Methylene Blue (EMB) agar, Thiosulphate Citrate Bile Salt (TCBS) agar, Glutamate Starch Pseudomonas (GSP) agar, Xylose Lysine Deoxycholate (XLD) agar and Cytophaga agar (CA). Bacterial identification was conducted using conventional biochemical tests and confirmed with a commercial identification kit. The antimicrobial resistance pattern was tested using a disk diffusion method, the heavy metal resistance pattern (cadmium, copper, mercury, and zinc) was determined using two-fold agar dilution method. The genomic properties of the bacteria were studied by a random amplified polymorphic DNA – polymerase chain reaction (RAPD-PCR). By using four primers (785, 786, 795, and OPA- 11), matrix data were analyzed using NTSYS software (version 2.1). Dendrogram constructed from unweighted pair-group method with arithmetic means (UPGMA).